2017
DOI: 10.21595/jve.2017.18537
|View full text |Cite
|
Sign up to set email alerts
|

Application of deterministic resampling particle filter to fatigue prognosis

Abstract: The method based on a particle filter for a fatigue crack growth prognosis has proved to be a powerful and effective tool for developing prognostics and health management (PHM) technology. However, the widely used basic particle filter have the unavoidable particle impoverishment problem, which will make particles unable to approximate the true posterior probability density function of the system state and lead to a prognosis result with a large error. This paper proposes a fatigue crack growth prognosis metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The application range of both methods is limited. To reduce calculation consumption and extend the application range of SIF, this paper uses a simplified version of the SIF range [19,27], as shown in Equation (3). ΔK=Δσsans-serifπa where Δ σ is the stress amplitude.…”
Section: State–space Model For Fatigue Crack Growthmentioning
confidence: 99%
See 3 more Smart Citations
“…The application range of both methods is limited. To reduce calculation consumption and extend the application range of SIF, this paper uses a simplified version of the SIF range [19,27], as shown in Equation (3). ΔK=Δσsans-serifπa where Δ σ is the stress amplitude.…”
Section: State–space Model For Fatigue Crack Growthmentioning
confidence: 99%
“…To take the uncertainty during fatigue crack growth into consideration, Zio et al [13] adopted the following revised model, as shown in Equation (5). normaldanormaldNf=10ωCfalse(tfalse)C(ΔK)m where ωCfalse(tfalse) is a zero-mean additive white Gaussian noise that follows Nfalse(0,σωC2false), denoting the uncertainty of material parameters during crack propagation, and σωC is the standard deviation [18,19,20]. The results of a large number of fatigue tests show that material parameters C and m have differences even with the same type of structure under the same working conditions, which characterizes the uncertainty of crack growth.…”
Section: State–space Model For Fatigue Crack Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…For further improvement, most studies are focused on improving particle resampling, usually based on traditional resampling mechanisms, such as hierarchical resampling [30], adaptive resampling [31][32][33], deterministic resampling [34][35][36], etc. Another way is to increase the diversity of samples by introducing intelligence optimization ideas, such as a genetic algorithm [37,38], firefly algorithm [39], bat algorithm [40] and so on.…”
Section: Introductionmentioning
confidence: 99%